A theoretical model for the effective thermal conductivity of silica aerogel composites. (5th January 2018) - Dai, Yan-Jun; Tang, Yu-Qing; Fang, Wen-Zhen; Zhang, Hu; Tao, Wen-Quan
Highlights: A theoretical model of the effective thermal conductivity is developed. The procedure accuracy is validated with the experimental results within ±10%. The influences of porosity, temperature and pressure are investigated. Best doping diameter and concentration exists which vary with temperature. Abstract: In the present paper, a complete engineering calculation procedure for fast evaluations of the effective thermal conductivity of the silica aerogel composites is developed as follows. First, the spherical hollow model is adopted to calculate the conductive thermal conductivity of pure silica aerogels. Then, a mixing model is used to consider the conduction enhancement effects of doped opacifiers and fibers. Next, the Mie theory is adopted to calculate the temperature-dependent Rosseland mean extinction coefficient of the aerogel composites, and the radiative thermal conductivity is obtained according to the Rosseland equation. Finally, the superposition of the conductive thermal conductivity and radiative thermal conductivity gives the total effective thermal conductivity of aerogel composites. To validate the accuracy of the present model, some corresponding experimental measurements are conducted based on the Hot Disk thermal constant analyzer, and the experiment data agree well with the theoretical calculation values. The maximum deviation is about ±10%. The influences of the temperature, pressure and the structure parameters on the prediction of the effective thermal conductivity are then investigated. To determine the dominant factor of the effective thermal conductivity, the contributions of gas, solid and radiation to the total effective thermal conductivity are investigated individually and some significant results are obtained.